Implementation of the 5C Financing Principle in Islamic Banking in the Perspective of the Qur'an - Syarif, Abdul Rifan; Setiadi, Iwan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research focuses on the implementation of the 5C principle of Islamic banking in the perspective of the Qur'an as one of the strengthening of the Islamic banking financial sector. The main problems raised are how the implementation of the 5C principle of financing in Islamic banking and how the implementation of the 5C principle in the perspective of the Qur'an. The method used in this research uses a mix method, namely library research and field research, namely research conducted through literature studies and sourced from various literature, tafsir, al- Qur'an, journals, as well as data taken from the field directly through interviews and data regarding the implementation of the 5C principle of financing at Bank Syariah Indonesia. By using a normative approach, namely analysing the implementation of the 5C principle in Islamic banking in accordance with the rules or norms in the Qur'an. The results of this study found that the implementation of the 5C principle in Islamic banking is no longer conceptualised as 5C namely character, capacity, capital, condition, and collateral but has been conceptualised into 5B namely mandate, knowledge, work, pious deeds, and borg / guarantee). The application of the 5B principle will be very good if implemented in accordance with the instructions in the Qur'an, especially in sharia-based banking. So that banking is not only labelled sharia, but also in terms and implementation has fulfilled the requirements of sharia, which has implications for the welfare of the world and the hereafter